The Stagnation of BASYARNAS in East Java, Indonesia: Islamic Legal Governance, Digital Invisibility, and the Practical Challenges of Sharia Arbitration - Ahmad Musadad; Holis Holis; Alfa Zaidanil Fauzi; Anis Nadia; R. Soeharjanto (Indonesian Journal of Islamic Law, 2026)
The rapid growth of sharia economic activity in East Java should have strengthened the role of the regional National Sharia Arbitration Board (BASYARNAS) as a trusted forum for resolving Islamic commercial disputes. In practice, however, Basyarnas East Java remains institutionally stagnant, having handled only seven cases in the last three years. This research note examines the practical causes of this stagnation through a socio-juridical approach grounded in Islamic legal governance. It argues that the weakness of Basyarnas East Java is not merely administrative but reflects a governance deficit that affects the institutional realisation of taḥkīm, maṣlaḥah, amānah, and al-ri‘āyah. The analysis identifies two interrelated problems: weak internal evaluation caused by leadership role overload and limited digital visibility in the public sphere. These conditions restrict legal dissemination (tablīgh), reduce public feedback mechanisms, and weaken the institution’s cognitive legitimacy among sharia economic actors. This note recommends strengthening procedural governance through clearer dual-role regulation, regular institutional evaluation, and the active use of participatory digital platforms. By linking practical institutional reform with Islamic legal reasoning, this note contributes to the development of adaptive sharia arbitration governance in contemporary Muslim society.